2017
DOI: 10.4172/2157-7633.1000395
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Enhancement of Cellular Adhesion in Bone Marrow Derived Mesenchymal Stem Cells (MSCs)

Abstract: Dopamine (DA) is a well-known neurotransmitter and critical element in the mussel adhesive protein that has gained increasing attention for its role in cellular growth enhancement in biomaterials, including cellular adhesion improvement. As the mechanism underlying this remains unclear, the objective of this study was to explore the effects of DA on the adhesion properties of bone marrow derived rat mesenchymal stem cells (rMSCs) using an hydroxyapatite gelatin nanocomposite biomaterial and to test whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…ECM-derived adhesion proteins and growth factors can efficiently attach to surfaces modified with DOPA 44,45. Studies have suggested that rMSC may be induced by nanotopographical signals through FA and actomyosin cytoskeleton contractility 46. The nanostructure and superior hydrophilicity of the surface material also induce cell adhesion 12,13,4749…”
Section: Discussionmentioning
confidence: 99%
“…ECM-derived adhesion proteins and growth factors can efficiently attach to surfaces modified with DOPA 44,45. Studies have suggested that rMSC may be induced by nanotopographical signals through FA and actomyosin cytoskeleton contractility 46. The nanostructure and superior hydrophilicity of the surface material also induce cell adhesion 12,13,4749…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the insertion of BNGF seems to exacerbate the effect of osteogenic stimulation. At the same time, the polydopamine coating improves calcium phosphate deposition owing to dopamine’s affinity for chelating calcium ions, thereby enhancing the inherent bioactivity of BGNF. Thus, the mesoporous and ion-releasing feature of BGNF associated with the osteogenic characteristic of polydopamine coatings inside the SF matrix creates biophysical and biochemical cues capable of promoting significant changes in the organization, morphology, differentiation, and cellular activity of the cytoskeleton.…”
Section: Resultsmentioning
confidence: 99%
“…[60] Several studies have previously demonstrated that free DA monomers can be detected in the space surrounding PDA. [61] To attain better physical and chemical properties, most researchers have used 150-500 μm DA to form PDA; therefore, a micromolar amount of DA can be expected to be released into the microenvironment around a PDA insertion site. [61][62][63][64][65] Caron et al studied a DA transporter (DAT) knockdown mouse model with which the relationship between DA and bone remodeling was revealed.…”
Section: Da Release From Pda In Regulating Bone Remodelingmentioning
confidence: 99%
“…[61] To attain better physical and chemical properties, most researchers have used 150-500 μm DA to form PDA; therefore, a micromolar amount of DA can be expected to be released into the microenvironment around a PDA insertion site. [61][62][63][64][65] Caron et al studied a DA transporter (DAT) knockdown mouse model with which the relationship between DA and bone remodeling was revealed. [66,67] The DAT is an important determinant of DA signaling activity as it is responsible for the rapid uptake of released DA into presynaptic terminals, which effectively removes extracellular DA and terminates its signaling.…”
Section: Da Release From Pda In Regulating Bone Remodelingmentioning
confidence: 99%
See 1 more Smart Citation